Extinction therapy and transcranial magnetic stimulation for the treatment of anxiety disorders - Ramírez-López, Alexa S.; Verdugo Díaz, Leticia (Horizonte Sanitario, 2023)
Objective: To describe the factors that can determine the reduction of symptoms in generalized anxiety and posttraumatic stress disorders by transcranial magnetic stimulation in combination with extinction therapy. Material and methods: A bibliographic review was conducted in databases (Cochrane, EBSCO, PubMed, ScienceDirect y Wiley), using the keywords: “transcranial magnetic stimulation”, “human” and “fear extinction”. A selection of clinical trials that used extinction therapy plus TMS and the skin conductance as variable quantified was made. Results: Five articles focused on the treatment of symptoms, like fear and recurrence of traumatic memories were obtained. There is little research on the topic. Stimulation protocols are heterogeneous between studies (stimulation frequency ranges from 1 to 30 Hz). Most of the studies reviewed reported the use of high-frequency stimulation. The maximum duration of therapeutic effects reported was one month. Conclusions: TMS and extinction therapy as a treatment for PTSD and GAD has a growing research field. Effectiveness results are not conclusive, sample sizes are small, and studies do not focus on which protocols are effective in the long-term. New studies that include patients with diagnosed PTSD and GAD are relevant to assess the protocols that have already been successful in healthy patients (fear-conditioned). Keywords: Anxiety; Conductance; Extinction; Fear; Post-traumatic stress.